Blood plasma protein profiles of neuropsychiatric symptoms and related cognitive decline in older people. Issue 2 (15th November 2022) - Rabl, Miriam; Clark, Christopher; Dayon, Loïc; Bowman, Gene L.; Popp, Julius
Abstract: Neuropsychiatric symptoms (NPS) severely affect patients and their caregivers, and are associated with worse long‐term outcomes. This study tested the hypothesis that altered protein levels in blood plasma could serve as biomarkers of NPS; and that altered protein levels are associated with persisting NPS and cognitive decline over time. We performed a cross‐sectional and longitudinal study in older subjects with cognitive impairment and cognitively unimpaired in a memory clinic setting. NPS were recorded through the Neuropsychiatric Inventory Questionnaire (NPI‐Q) while cognitive and functional impairment was assessed using the clinical dementia rating sum of boxes (CDR‐SoB) score at baseline and follow‐up visits. Shotgun proteomic analysis based on liquid chromatography‐mass spectrometry was conducted in blood plasma samples, identifying 420 proteins. The presence of Alzheimer's Disease (AD) pathology was determined by cerebrospinal fluid biomarkers. Eighty‐five subjects with a mean age of 70 (±7.4) years, 62% female and 54% with mild cognitive impairment or mild dementia were included. We found 15 plasma proteins with altered baseline levels in participants with NPS (NPI‐Q score > 0). Adding those 15 proteins to a reference model based on clinical data (age, CDR‐SoB) significantly improved the prediction of NPS (from receiver operating characteristic area under the curve [AUC] 0.75 to AUC 0.91, p = 0.004) with a specificity of 89% and a sensitivity of 74%. The identified proteins additionally predicted both persisting NPS and cognitive decline at follow‐up visits. The observed associations were independent of the presence of AD pathology. Using proteomics, we identified a panel of specific blood proteins associated with current and future NPS, and related cognitive decline in older people. These findings show the potential of untargeted proteomics to identify blood‐based biomarkers of pathological alterations relevant for NPS and related clinical disease progression. Abstract : Using untargeted proteomics we identified 15 plasma proteins associated with neuropsychiatric symptoms (NPS) in cognitively mildly impaired and unimpaired older participants in a memory clinic study. Compared to a reference model, adding the 15 plasma proteins significantly improved the prediction of NPS at baseline (a) and at follow‐up over 36 months (b). Plasma protein biomarkers may be useful for the prediction of persisting NPS. These findings open the perspective for early detection and interventions to reduce NPS and improve long term clinical outcomes in memory clinic patients.